Application of Moringa Oleifera Seed Powder For Iron (III) Coagulation on Local Water Resources - Fadillah Utami Prasetyaningtyas; Barlah Rumhayati; Masruri Masruri (The Journal of Pure and Applied Chemistry Research, 2013)
This research aims to know the effect of the use of powder moringa seed to coagulant mass and coagulation process, and its effectiveness to increase the quality of pure water. This research uses factorial research design and statistic test MANOVA. To analyse water quality, the researcher uses Fe parameter.  A graphic of coagulant mass and time for each parameter is used to analyse the data. Based on the research result, the uses of moringa seed as coagulant in each 300 mL mineral water gives a possitives result to the river water sample using 100 mg coagulant mass and sedimentations time for 60 minutes, well water sample using 500 mg coagulant mass and sedimentations time for 60 minutes, tap water sample using 300 mg  coagulant mass and sedimentations time for 90 minutes. The effective coagulant that increase the water quality on well water is 98,32% of moringa seed powder, on river water is 96,64%  and for tap water is 25,62%.